Letter from Marianne Homburger to Max Bredig, January 10, 1938 - Homburger, Marianne (1938)
Marianne Homburger (1903-1986) writes to Max Albert Bredig (1902-1977) about their family leaving Germany. Marianne writes that their father, Georg Bredig (1868-1944), could go to England if Max is able to support him financially. She also gives updates that her step-children are registered for the Kindertransport. Marianne ends the letter telling Max that she hopes he is well because he is their only ray of hope.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Kindertransports (Rescue operations); Bredig, Georg, 1868-1944; Homburger, Viktor, 1888-1968; World War (1939-1945); Jewish Holocaust (1939-1945); Third Reich